2011
DOI: 10.1017/s0033291711001541
|View full text |Cite
|
Sign up to set email alerts
|

The effects of puberty on genetic risk for disordered eating: evidence for a sex difference

Abstract: Background Differences in genetic influences on disordered eating are present across puberty in girls. Heritability is 0% before puberty, but over 50% during and after puberty. Emerging data suggest that these developmental differences may be due to pubertal increases in ovarian hormones. However, a critical piece of evidence is lacking, namely, knowledge of genetic influences on disordered eating across puberty in boys. Boys do not experience increases in ovarian hormones during puberty. Thus, if pubertal inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
89
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(96 citation statements)
references
References 46 publications
(111 reference statements)
7
89
0
Order By: Relevance
“…There are also differences in risk across sex. For example, puberty appears to influence the heritability of disordered eating in girls but not boys (Klump, Culbert, Slane, Burt, Sisk, & Nigg, 2011). Further investigation of similarities and differences in eating disorder risk by sex are clearly warranted.…”
Section: Discussionmentioning
confidence: 99%
“…There are also differences in risk across sex. For example, puberty appears to influence the heritability of disordered eating in girls but not boys (Klump, Culbert, Slane, Burt, Sisk, & Nigg, 2011). Further investigation of similarities and differences in eating disorder risk by sex are clearly warranted.…”
Section: Discussionmentioning
confidence: 99%
“…These same effects may underlie sex differences in risk, where in males, elevated prenatal testosterone exposure masculinizes the central nervous system and increases sensitivity to testosterone during puberty (Wade, 1972). Increased responsiveness to testosterone during puberty may further contribute to a “male-like” nervous system that protects against genetic and phenotypic activation of DE attitudes during and after mid-puberty (Klump et al, 2012). …”
Section: Discussionmentioning
confidence: 99%
“…Klump et al (388), as well as others (27,631,715) have also investigated the biological contributions to the sharp increases in the incidences of bulimia nervosa and binge-eating disorder that occur in girls at the onset of puberty (ϳ8 -10 yr of age). In the Klump et al study (388), they found 1) no detectable heritability of disordered eating in prepubertal girls; 2) heritability of ϳ0.5 in girls during and after puberty; and 3) heritability of ϳ0.5 in boys at all times. In another study (393), they detected significant heritability for disordered eating in 10 -15-yr-old girls with higher plasma estradiol levels, but not in girls with lower estradiol levels.…”
Section: R1245 Sex Differences In the Physiology Of Eatingmentioning
confidence: 93%